Implementation of Principal Leadership in Improving the Quality of Education Based on Iasp 2020 at MIN 2 Bandung City - Ahsyaf Muzakki; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article is written to see the leadership of the principal in improving the quality of education. The research method used in writing this article is a qualitative method with a descriptive approach. Data collection techniques are carried out through: first, in-depth interviews; second, participant observation and third, documentation. While the data collected through the three techniques above are then checked for validity by checking credibility. The results of the study of the type of principal leadership in improving the quality of education at MIN 2 Bandung City use namely by prioritizing cooperation in implementing leadership. The obstacles faced in improving the quality of education are the lack of educational facilities and infrastructure. These educational facilities and infrastructure greatly affect the learning process. Efforts to improve the quality of education are carried out by developing teacher competencies, meeting the needs of school stakeholders and getting used to working together in solving problems.